Aplikasi Lapak Sarah (Layanan Pengajuan Adminduk Desa Kelurahan) Meningkatkan Kualitas Pelayanan Publik di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Blitar - Fitriani, Ami; Swasono, Edy (Otonomi, 2024)
Research regarding Analysis of the Lapak Sarah Application in improving the quality of public services at the Blitar Regency Population and Civil Registration Service has significant relevance and can make a real contribution to efforts to improve public services at the regional level. This research is qualitative research where data collection uses interviews with several informants. The results of the research show that officers have been able to understand each stage and procedure for running the Lapak Sarah application to improve the quality of service, the Lapak Sarah Application in its implementation has been able to support the timely completion of documents to improve the quality of service at the Blitar Regency Population and Civil Registration Service, the Lapak Sarah Application has helped improve the quality of population administration services at the Blitar Regency Population and Civil Registration Service, the Lapak Sarah Application in improving population administration services at the Blitar Regency Population and Civil Registration Service has been achieved, the Lapak Sarah Application has made the process of population administration services at the Blitar Regency Population and Civil Registration Service experienced changes which is real in improving the quality of services at the Blitar Regency Population and Civil Registration Service